PERBANDINGAN POTENSI ANALGESIK VARIASI EKSTRAK ETANOL DAN EKSTRAK N-HEKSANA DAUN PEPAYA (Carica papaya L.): Comparison Of The Analgesic Potential Of Variations Of Ethanol Extract And N-Hexane Extract Of Papaya Leaves (Carica Papaya L) - Herlina Ramadhani; Ade Maria Ulfa; Tutik Tutik (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2026)
Abstract This research aimed to test and compare the analgesic effectiveness of n-hexane and ethanol extracts of papaya leaves in mice (Mus musculus) at doses of 400 mg/kgBB and 800 mg/kgBB. Maceration extraction resulted in a yield of 5.06% (n-hexane) and 8.5% (ethanol). Phytochemical screening showed that both extracts were positive for flavonoids and steroids. The analgesic test was conducted using the acetic acid induction method by observing the number of writhing movements. The test groups included a negative control, a positive control (mefenamic acid), and n-hexane and ethanol extracts at the two aforementioned doses. The results showed that all extract groups significantly reduced writhing compared to the negative control (p<0.05). The percentage of protection for n-hexane was 69.44% (400 mg) and 74.12% (800 mg), while ethanol achieved 83.5% (400 mg) and 88.56% (800 mg). The positive control provided 97.23% protection. ANOVA demonstrated a significant difference between the groups (p=0.000). Post hoc tests confirmed that the 800 mg/kgBB ethanol extract was the most effective among the tested extracts, with no significant difference from the positive control. Keywords: Analgesic, Carica papaya, Ethanol Extract, n-Hexane Extract, Mice